Financial Literacy for Women SHG in Mainstream Finance - Gupte, Shruti (Digital Repository of Theses - SSBM Geneva, 2024)
The goal of this thesis is to determine the level of financial literacy among women who are members of Self-Help Groups (SHGs) in rural India. It also investigates how financial literacy affects microfinance services such as credit, savings, and insurance, and how demographic characteristics such as education, income, and social capital impact financial literacy and the use of microfinance services among SHG women. The survey was conducted on a sample size of 360 respondents, with 60 respondents selected from each of the six identified states in six zones of the country. Based on the pilot survey results, the survey instruments such as the questionnaire and instruction set were finetuned, and outcomes were derived. The survey included four sets of questions, namely, demographic and socio-economic characteristics of the response domain, financial literacy, financial inclusion, and measuring financial literacy, inclusion, and well-being. The survey revealed the following findings on financial literacy: 1. Only 24% of rural and 33% of urban respondents were found to be financially literate. 2. Respondents aged 18-29 years were the most financially literate in their age category. 3. The prevalence of financial literacy was higher among respondents with higher levels of education and income. 4. Government employees exhibited the highest prevalence of financial literacy in the occupation category. The survey also revealed the following findings on financial inclusion: 1. Urban respondents were found to be more financially included than rural respondents. 2. Young respondents aged 18-29 years were more financially included than older respondents. 3. Respondents belonging to the General category were found to be ahead of other social categories in financial inclusion. 4. Financial inclusion was found to be higher among respondents with higher levels of education. 5. Government employees were found to be more financially included than respondents from other occupations. 6. The prevalence of financial inclusion was higher among respondents with higher income levels.